1970
DOI: 10.1104/pp.46.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Fat Metabolism in Higher Plants

Abstract: To understand more fully organelle membrane assemblage, the synthesis of the first fatty acids by the germinating pea, Pisum sativum, was studied by the incorporation of either tritiated water or acetate-1_'4C into lipids by the intact, initially dry seed. After a lag phase, labeling proceeded linearly. This lag phase ended when uptake of water had increased the seed weight to 185% of its original weight. The first fatty acids synthesized were palmitic and stearic followed shortly after by long chain saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 42 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…TLC-FID separation of PL revealed that PC was the major PL (70% of total) of borage seeds prior to germination ( Table 6). PC is also the major PL in seeds of alfalfa (Medicago sativa) (20), pea (Pisum sativum) (14,44), barley (Hordeum vulgare) (19), saf- flower (Carthamus tinctorius) (8), and soybean (Glycine max) (42). PS and PE were coeluted and their total made up the nextlargest fraction.…”
Section: Resultsmentioning
confidence: 99%
“…TLC-FID separation of PL revealed that PC was the major PL (70% of total) of borage seeds prior to germination ( Table 6). PC is also the major PL in seeds of alfalfa (Medicago sativa) (20), pea (Pisum sativum) (14,44), barley (Hordeum vulgare) (19), saf- flower (Carthamus tinctorius) (8), and soybean (Glycine max) (42). PS and PE were coeluted and their total made up the nextlargest fraction.…”
Section: Resultsmentioning
confidence: 99%
“…If CH indeed penetrated and inhibited protein synthesis in the same cells synthesizing these enzymes, the increases in activities of OMP pyrophosphorylase, OMP decarboxylase, and probably of cytidine deaminase during germination are likely due to activation rather than actual synthesis. Enzymes capable of fatty acid formation (8) and an amylopectin-1,6-glucosidase (11) similarly increase in activity in cotyledons of germinating peas without being synthesized de novo. However, assuming the only important effect of CH upon increase of uridine hydrolase activity resulted from inhibition of protein formation, this enzyme probably arises at least in part from de novo synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…No influences upon respiration were observed after exposure to 50 pg of CH per ml. Harwood and Stumpf (8) studied the influence of various concentrations of CH up to 1 mg/ml upon water absorption, fatty acid synthesis, and leucine-14C incorporation into protein of whole pea seeds during the first 24 hr of germination. CH had no effect on imbibition, consistent with our unpublished data, but leucine incorporation during the first 24 hr of germination was inhibited about 78% by 10 or 25 ,ug of CH per ml.…”
Section: Discussionmentioning
confidence: 99%
“…plates with chloroform/methanol/acetic acid (200: 100: 1, by vol.) and were identified after paper chromatography of their deacylated derivatives (Dawson, 1960) and acid hydrolysates (Harwood & Stumpf, 1970). Amounts of acyl lipids were determined from their fatty acid content.…”
Section: Lipid Extraction and Analysismentioning
confidence: 99%